Intrapartum Asymptomatic Congenital Complete Heart Block; Case Study and Literature Review - Muneera AlTaweel; Sarah AlMukhaylid; Nada Alsultan; Abdulmalik AlAbdulqader; Abdulwahab Alkhashram; Fahad Memon; Waleed Gado; Khalid AlIbrahim (Innovative Journal of Medical and Health Sciences, 2022)
Congenital complete heart block (CCHB) might be unnoticed for a long time. Often, 30 percent are discovered incidentally during pregnancy without any symptoms; patients should be evaluated further to determine the current and long-term care plan. We describe a case of a 42-year-old pregnant woman who developed pre-eclampsia during her third trimester of pregnancy and was later discovered to have CCHB. Throughout her life, she enjoyed a regular life free of symptoms. Asymptomatic complete heart block (CHB) should be thoroughly investigated to ascertain its type. Temporary or permanent pacemakers should be considered on an individual basis, depending on the clinical status, investigations, and long-term prognostic concerns.